Hill Agriculture: Marketing of Vegetables in Nainital District, Uttarakhand - Choudhary, Harshika; Saryam, Ritu Shah, Manohar (Indian Journal of Hill Farming, 2018)
Though India has emerged as a major producer of horticultural crops and the share of horticulture in the economy has been increasing, there is still a lot of scope in harnessing the potential of this sector. Sectors like horticulture (both fruit and vegetable cultivation) have a comparative advantage in the hilly region due to its agro-climatic conditions. The study was conducted in Dhari block of Nainital district, Uttarakhand. Both primary and secondary data was collected for the study purpose. Four vegetables covering maximum area under vegetable cultivation was selected. On this basis, pea, cabbage, french bean and tomato are selected for the study. There is only one major marketing channel prevailing in the study area, Haldwani mandi itself and same was used by majority of the sample farmers for selling their produce. Channel-I was found out to be the major marketing channel, as 89.74 per cent of the total farmers growing pea, 90.62 per cent of the total farmers growing cabbage and 89.28 per cent of the total farmers growing tomato were selling their produce through channel-I.